Lactoferrin acute-phase protein and proteinase inhibitors in blood of patients with Q-wave myocardial infraction complicated by acute heart failure - K. P. Belokoneva; N. A. Bichan (Бюллетень сибирской медицины)
153 patients with Q-wave noncomplicated and complicated myocardial infraction have been examined. Blood serum was studied for acute-phase proteins (alfa-2-macroglobulin (MG), alfa-1-antitrypsin (ATr), and lactoferrin (LF)) in 97 patients ((57.9 ± 1.06) years old). Blood was sampled at the 1st, 7th, and 14th days after myocardial infraction. The decrease of MG in acute phase was observed in patients with cardiogenic shock. Increased concentrations of LF and unchanged MG level at the 1—7 days were observed at pulmonary edema.